Tolerance of castor bean cultivars under salt stress - Francisco V. da S. Sá; Emanoela P. de Paiva; Evandro F. de Mesquita; Antonio M. P. Bertino; Marcelo A. Barbosa; Lauter S. Souto (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to evaluate the tolerance of castor bean cultivars under salt stress during the initial growth stage. The experiment was set in randomized blocks, in a 5 x 4 factorial scheme, resulting in 20 treatments, 5 salinity levels (0.6-control, 1.2, 1.8, 2.4 and 3.0 dS m-1) and 4 castor bean cultivars (BRS Energy, LA Guarani, BRS Gabriela and IAC 028)] with 3 replicates. At 30 days after sowing, plants were evaluated for growth, dry matter accumulation and salt tolerance. Increased salinity levels in the water used for irrigation reduced the growth of all the studied cultivars. The salt tolerance of the studied castor bean cultivars follows the following order: BRS Energia > BRS Gabriela = IAC 028 > LA Guarani.